2021
DOI: 10.1063/5.0052479
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous choline amino acid deep eutectic solvents

Abstract: We have investigated the structure and phase behavior of biocompatible, aqueous deep eutectic solvents by combining choline acetate, hydrogen aspartate, and aspartate amino acid salts with water as the sole molecular hydrogen bond donor. Using contrast-variation neutron diffraction, interpreted via computational modeling, we show how the interplay between anion structure and water content affects the hydrogen bond network structure in the liquid, which, in turn, influences the eutectic composition and temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…9 Recently, a special issue of the Journal of Chemical Physics titled "Chemical Physics of Deep Eutectic Solvents" was launched, to which the reader is referred for more information on DESs. [10][11][12][13][14][15][16][17][18][19] DESs and ionic liquids (ILs) are often regarded as superior solvents compared to volatile organic compounds (VOCs) due to a negligible vapor pressure at room temperature. 2,5,6,20 Such a low vapor pressure would limit the emission and loss of the DESs into the atmosphere and may facilitate the removal of solutes from DESs by distillation.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, a special issue of the Journal of Chemical Physics titled "Chemical Physics of Deep Eutectic Solvents" was launched, to which the reader is referred for more information on DESs. [10][11][12][13][14][15][16][17][18][19] DESs and ionic liquids (ILs) are often regarded as superior solvents compared to volatile organic compounds (VOCs) due to a negligible vapor pressure at room temperature. 2,5,6,20 Such a low vapor pressure would limit the emission and loss of the DESs into the atmosphere and may facilitate the removal of solutes from DESs by distillation.…”
Section: Introductionmentioning
confidence: 99%
“…Between the two comprehensive studies, 23,27 values reported by De Santis et al are significantly higher than those of Liu et al The former is more widely supported by other studies such as ChAsp, Ch 2 Asp and ChArg being room temperature solids. 28,29 Despite the differences in reported values, it is generally agreed that most ChAAILs are highly viscous, making them difficult to handle under room conditions. The presence of additional hydrogen bonding sites on the amino acid side chains, such as Asp − , Arg − , Glu − , His − , etc ., seems to further increase viscosity.…”
Section: Preparation and Physical Propertiesmentioning
confidence: 99%
“…100 Studies have shown that water forms short, linear hydrogen bonds with amino acid anions. 29,101 Therefore, water is likely to compete with hydrogen bonds among ions and weaken the lubricant film at the interface, ultimately leading to the dissolution of amino acid, and cleavage of the lubricant film. This is supported by the observation that the effectiveness of ChPro as a lubricant correlates with water content.…”
Section: Lubricationmentioning
confidence: 99%
See 2 more Smart Citations